The pattern of FP-CIT PET in pure white matter hyperintensities–related vascular parkinsonism - Lee, Yang Hyun; Lee, Sangwon; Chung, Seok Jong; Yoo, Han Soo; Jung, Jin Ho; Baik, Kyoungwon; Ye, Byoung Seok; Sohn, Young H.; Yun, Mijin; Lee, Phil Hyu (Parkinsonism & related disorders, 2021)
To determine whether vascular parkinsonism (VaP) patients with visually normal dopamine transporter (DAT) scans have presynaptic dopaminergic depletion. We enrolled 23 VaP patients who had parkinsonism, relevant diffuse subcortical white matter hyperintensities (WMH), and visually normal DAT scans, 23 Parkinson's disease (PD) patients, and 31 control subjects. By quantitatively analyzing 18F–N-(3-fluoropropyl)-2β-carbon ethoxy-3β-(4-iodophenyl) nortropane (18F-FP-CIT) positron emission tomography, we compared the pattern of striatal DAT availability among groups. The discriminatory power of striatal DAT availability to differentiate VaP patients from control subjects or PD patients was assessed using receiver operating characteristics (ROC) analyses. Additionally, correlation analysis was performed to determine whether WMH severity or Unified Parkinson Disease Rating Scale Part III (UPDRS-III) score is related to presynaptic dopaminergic depletion in VaP. VaP patients exhibited decreased DAT availability in all striatal subregions, including posterior putamen, compared to control subjects. VaP patients and control subjects had similar patterns of anteroposterior and ventrodorsal DAT gradients in caudate and putamen level, but VaP patients exhibited significantly different patterns at putamen level, relative to PD patients. The severity of periventricular WMH was significantly correlated with all substriatal DAT availability in VaP, but not with UPDRS-III scores. The ROC analysis showed that DAT availability in caudate and posterior putamen had a fair discriminatory power when differentiating VaP patients from control subjects. This study demonstrates that VaP patients with WMH exhibited diffusely decreased DAT availability without any specific regional gradients of DAT patterns distinct from either control subjects or PD patients. •VaP with normal DAT scan exhibited decreased striatal SNBRs compared to controls.•Unlike PD, VaP had a more diffuse loss of DAT availability across whole striatum.•Severity of periventricular WMH was correlated with all substriatal SNBRs in VaP.•SNBRs of AC, PC, and PP had a fair accuracy when discriminating VaP from controls.